Diabetic Nephropathy: Advancement in Molecular Mechanism, Pathogenesis, and Management by Pharmacotherapeutics and Natural Compounds - Shivam; Gupta, Asheesh Kumar; Kumar, Sushil; Kumar, Hitesh (Natural Products Journal, The, 2025)
The primary cause of End-stage Renal Disease (ESRD) and a possible chronic microvascular consequence of diabetes mellitus is Diabetic Nephropathy (DN). The early stages of diabetic kidney disease (DN) often include hyperfiltration and albuminuria, which are followed by a steady loss in renal function. Diabetes patients may display the usual signs and symptoms of Diabetic Kidney Disease (DKD), particularly if they have Type 2 Diabetes Mellitus (T2DM). Significant confounders might also include the presence of other glomerular/tubular illnesses and severe peripheral vascular disease. Patients with diabetic nephropathy have an all-cause mortality rate that is approximately thirty times higher than that of diabetic patients without nephropathy. Most patients with diabetic nephropathy die from cardiovascular disease before they develop End-stage Renal Disease (ESRD). The formation of diabetic nephropathy must be prevented and its advancement must be slowed by controlling metabolic and hemodynamic abnormalities. Research should concentrate on developing new therapies for diabetic nephropathy since it is a crippling condition that affects people worldwide and causes significant social and economic burdens. Recent findings suggest that numerous pathways are activated during diabetes mellitus and that these pathways individually or collectively play a role in the induction and progression of diabetic nephropathy. However, clinical strategies targeting these pathways to manage diabetic nephropathy remain unsatisfactory, as the number of diabetic patients with nephropathy is increasing yearly. To develop ground-breaking therapeutic options to prevent the development and progression of diabetic nephropathy, a comprehensive understanding of the molecular mechanisms involved in the pathogenesis of the disease is mandatory. Therefore, the purpose of this paper was to discuss the underlying mechanisms and downstream pathways involved in the pathogenesis of diabetic nephropathy.
Keywords: renal fibrosis